2016
DOI: 10.1177/1369433216646018
|View full text |Cite
|
Sign up to set email alerts
|

Designing optimal tuned mass dampers using improved harmony search algorithm

Abstract: In this article, the optimum parameters of tuned mass dampers for suppressing the dynamic responses of multi degree-of-freedom structures induced by base excitations are proposed. The improved harmony search algorithm, which has been successfully applied in many fields, is used for tuning the tuned mass dampers under seismic loading. The parameters of tuned mass dampers including mass, damping coefficient, spring stiffness, and location are assumed as design variables and two objective functions have been cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Den Hartog [1] obtained analytical solution for the TMD with dashpot element called the traditional TMD. This study was followed by other works that suppressing the resonant vibrations of the main structure due to various excitations [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. These works indicate that a TMD device yields a higher level of control performance in suppressing the vibrations of the main structures.…”
Section: Introductionmentioning
confidence: 91%
“…Den Hartog [1] obtained analytical solution for the TMD with dashpot element called the traditional TMD. This study was followed by other works that suppressing the resonant vibrations of the main structure due to various excitations [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. These works indicate that a TMD device yields a higher level of control performance in suppressing the vibrations of the main structures.…”
Section: Introductionmentioning
confidence: 91%
“…Bekda and Nigdeli [44] proposed using harmony search algorithm to find the best parameters for tuned mass dampers. Yazdi et al [45] proposed an improved harmony search algorithm for designing tuned mass dampers, and it is found that the improved harmony search algorithm is more efficient than the gene algorithm and the particle swarm optimization algorithm. Nigdeli and Alhan [46] optimized the parameters of the seismic isolation system through the harmony search algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…19 Alternatively, the optimal design of a TMD for the damped structure has been obtained with numerical optimization methods. 13,[20][21][22] For the methods mentioned above, the optimal results were obtained by assumptions of deterministic structural parameters and external excitations. However, the deterministic assumptions of a structural system and excitation may lead to a considerable reduction of the design performance.…”
Section: Introductionmentioning
confidence: 99%